CALCULATION OF 17O NMR SHIELDINGS IN MOLECULAR MODELS FOR CRYSTALLINE MO, M=MG, CA, SR, AND IN MODELS FOR ALKALINE EARTH SILICATES - Tossell J.A. (My University, 2004)
17O NMR shieldings are calculated for the central O in the molecular model OM6(OH)12-2, for crystalline alkaline earth oxides, MO, where M=Mg, Ca, and Sr, using both Hartree-Fock and hybrid Hartree-Fock density-functional theory. Agreement of calculated and experimental NMR shifts of CaO and SrO compared to MgO is good, but only if the basis set on the M atoms has sufficient tight d polarization functions. Preliminary results are also presented for nonbridging O in the silicate Si(OH)3O- anion, perturbed by alkaline earth cations, giving trends which agree qualitatively with experiment.
Keywords: MGO; CAO; SRO; NMR; ALKALINE EARTH SILICATES; QUANTUM CALCULATION